Effect on solvent polarity and concentration on the photo transformation of 6-nitro BIPS - Abdul Aziz Nazri, Shamsul Azrolsani Abdul Aziz Nazri; Abdul Malek a,, Mohamad Zahid Abdul Malek a,; Mat Tamizi Zainuddin, Mat Tamizi Zainuddin; Mohamed Islam , Noor Zalikha; Wahid, Zaharah (2012)
Polar and non-polar solvents; ethanol and toluene respectively were used to dissolve and investigate the photochromism behavior of 6-nitro BIPS at different solvent concentration. Absorption spectra of 6-nitro BIPS in low concentration solvent were arising to absorption peak of 530nm and 600nm after UV irradiation for ethanol and toluene respectively. At high concentration solvent of 6-nitro BIPS, the absorption spectra did not present any changes on absorption peak after UV irradiation whereas the absorption peak was remains at 530nm for ethanol and no absorption peak appeared for toluene. Shifting of 6-nitro BIPS wavelength spectrum from 530nm for dilution in ethanol to 600nm for dilution in toluene in low concentration solvent was observed and investigated.